WD repeat domain 5 promotes the development of late-onset preeclampsia by activating nuclear factor kappa B - Xudong Zhao; Fengyun Su; Fanhua Kong; Juan Su; Xiaojing Yang; Lei Li; Aihua Li; Qinwen Li (Acta Cirúrgica Brasileira, 2023)
ABSTRACT Purpose: Over-activation of nuclear factor kappa B (NF-κB) was proven to be involved in the pathogenesis of preeclampsia. However, its regulation mechanism is not clear yet. This paper explored the role of WD repeat domain 5 (WDR5) in the development of late-onset preeclampsia and its relationship with NF-κB. Methods: WDR5 expression was detected in normal placentas and placentas from late-onset preeclampsia patients. CCK-8 and colony formation assays were conducted to appraise the proliferative ability of trophoblast. Migration and invasion were observed by wound healing and transwell assays. The interaction between WDR5 and NF-κB inhibitor I-kappa-B-alpha (IkBa) was verified by Co-immunoprecipitation analysis. Immunofluorescence was used to analyze the activation of NF-κB. Finally, we tested the role of WDR5 using the mice late-onset preeclampsia model. Results: WDR5 was highly expressed in the placentas of late-onset preeclampsia patients. WDR5 overexpression suppressed cell proliferation, migration, and invasion in trophoblast. WDR5 could interact with IkBa to activate NF-κB. Knockdown of NF-κB counteracted the anti-proliferative and anti-metastatic effects of WDR5 overexpression in trophoblast. In-vivo studies suggested that targeting WDR5 combated late-onset preeclampsia development. Conclusions: Our finding provides new insights into the role of WDR5 in late-onset preeclampsia development.